Reimbursing Health Plans and Health Providers: Efficiency in Production versus Selection - Newhouse, Joseph P. (Journal of Economic Literature, 1996)
The tradeoff between an insurer's or medical provider's incentives to select good risks and to produce efficiently is governed by the supply-price analog to the demand-price tradeoff between moral hazard and risk aversion. Under a variety of models the optimum supply price is a mixture of capitation and fee-for-service payments. Empirical literature shows that pure capitation payment leaves strong incentives for selection that are acted upon. The presence of contracting costs in a Rothschild-Stiglitz model means a limited pooling equilibrium can exist and that poor risks will not be at their preferred outcome.